2018
DOI: 10.1080/13607863.2018.1464116
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of nursing home staff using the targeted interdisciplinary model for evaluation and treatment of neuropsychiatric symptoms (TIME) – a qualitative study

Abstract: TIME shifts the way of learning for the staff from a traditional to a more innovative and reflection-based learning through a process of learning how to learn at work. The staff's experienced increased coping in their approach to complex problems. Our results emphasise the importance of a structured and biopsychosocial approach to NPS in clinical practice. Future research should explore models for integrating situated learning in daily routines in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
0
31
0
2
Order By: Relevance
“…However, previous research has also indicated that abusive behaviour can be understood as less abusive when the victim has dementia, and for that reason it is often not reported [17,48]. Recognising that aggressive behaviour has a multifactorial aetiology, best practice recommendations [49] and research evidence [50,51] call for a comprehensive biopsychosocial approach that investigates the resident's unmet needs, medical conditions, environmental factors, and interactions between residents and caregivers and a tailored response [49]. Care managers' perceptions of resident-to-resident aggression as normal and a foreseeable risk, places residents at risk and is also a failure to deliver much needed care to the initiator.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has also indicated that abusive behaviour can be understood as less abusive when the victim has dementia, and for that reason it is often not reported [17,48]. Recognising that aggressive behaviour has a multifactorial aetiology, best practice recommendations [49] and research evidence [50,51] call for a comprehensive biopsychosocial approach that investigates the resident's unmet needs, medical conditions, environmental factors, and interactions between residents and caregivers and a tailored response [49]. Care managers' perceptions of resident-to-resident aggression as normal and a foreseeable risk, places residents at risk and is also a failure to deliver much needed care to the initiator.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive behaviour is not always a problem to be solved, but requires competent nursing‐personnel with the ability to be present in the situation, with the resident and recognize the person behind the behaviour (Bondas, ; Rokstad et al., ). One must find individual solutions for individual residents, because each symptom works in its unique way on the unique person in its specific social context (Lichtwarck et al., , ). Caregivers’ feelings of powerlessness in events with aggression can be caused by their expectations to “manage” more than is possible and by underestimating the good that they do (Lichtwarck et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…To manage behavioural and psychological symptoms of dementia that often result in episodes of RRA, a study by Lichtwarck et al [65] found that a multicomponent biopsychosocial approach (TIME) significantly reduced the agitation of residents in nursing homes. Moreover, staff who used TIME experienced increased coping in their approach to residents with complex neuropsychiatric symptoms [66]. In addition to educational programs for staff, nursing homes should emphasise on procedures and structures within the organisation e.g.…”
Section: Discussionmentioning
confidence: 99%